Instant Organoleptic Test of Ginger from Three Ginger Varieties (Zingiber officinale): Uji Organoleptik Instan Jahe dari Tiga Varietas Jahe (Zingiber officinale) - Herawati, Jajuk; Thohiron, Mochamad; Toheri, Toheri; Dhinata, Yhogga Pratama (Journal of Applied Plant Technology, 2024)
Instant organoleptic test of ginger against three varieties of ginger (Zingiber officinale) is descriptive research. The purpose of this study is to examine the feasibility of processed ginger formulations and their effect on the level of preference of panelists as consumers for instant ginger as an herbal drink made from raw materials with three varieties of ginger. This research was conducted in May-July 2023 at the Production Laboratory of the Faculty of Agriculture-UWKS using a one-factor Complete Randomized Design (RAL) consisting of 3 levels. The treatment is the use of the main raw materials of ginger with 3 varieties, namely J1 = elephant ginger (2023 research results); J2 = red ginger; J3 = empirrit ginger. The observation parameters were carried out through Organoleptic tests on product properties, namely taste, aroma, texture, color, physical appearance, and knowing the level of preference of panelists for ginger instant drinks from 3 varieties of ginger, and each treatment was repeated three times with 10 panelists each repeat. This hedonic test with sensory analysis of instant ginger products is used to guess what products the panelists like the most with the level of liking. The method used in this Hedonic Test, consists of 5 levels: (1) very dislike, (2) dislike, (3) ordinary, (4) like, and (5) very like From the results of this study is expected to provide benefits to the public in consuming ginger as a healthy herbal drink, as well as for other researchers who are interested in similar research. Three levels in the treatment of the use of three varieties of ginger on instant results of ginger, from organoleptic tests give results that elephant ginger has advantages in aroma and color, empirrit ginger has the advantage of soft texture and red ginger has a good taste.